Milling parameter optimization for refinement of NiO/Al mixtures and synthesis of Ni/Al2O3 nanocomposites. - Berramdan, Nor El-houda; Boutefnouchet, Hafida; Zidani, Mosbah; Yamanoglu, Ridvan; Curfs, Caroline (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
<span lang="EN-GB" style="font-size: 12.0pt; line-height: 115%; font-family: ’Times New Roman’,serif; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-GB;">This study examined the effect of milling parameters on the development of Ni/Al2O3 nanocomposite<span style="font-size: 12.0pt; line-height: 115%; font-family: ’Times New Roman’,serif; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-US;">s<span lang="EN-GB" style="font-size: 12.0pt; line-height: 115%; font-family: ’Times New Roman’,serif; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-GB;"> and refinement of NiO and Al powders. Ball milling of certain mixtures<span style="font-size: 12.0pt; line-height: 115%; font-family: ’Times New Roman’,serif; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-US;"> was<span lang="EN-GB" style="font-size: 12.0pt; line-height: 115%; font-family: ’Times New Roman’,serif; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-GB;"> followed by sintering at 800 and 1100 °C for 2 h. The X-ray diffraction results of the dry-milled powders <span style="font-size: 12.0pt; line-height: 115%; font-family: ’Times New Roman’,serif; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-US;">indicated <span lang="EN-GB" style="font-size: 12.0pt; line-height: 115%; font-family: ’Times New Roman’,serif; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-GB;">that increasing the ball-to-powder weight ratio <span style="font-size: 12.0pt; line-height: 115%; font-family: ’Times New Roman’,serif; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-US;">from 20:1 <span lang="EN-GB" style="font-size: 12.0pt; line-height: 115%; font-family: ’Times New Roman’,serif; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-GB;">to 42:1 produced finer particles<span style="font-size: 12.0pt; line-height: 115%; font-family: ’Times New Roman’,serif; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-US;">, resulting in the <span lang="EN-GB" style="font-size: 12.0pt; line-height: 115%; font-family: ’Times New Roman’,serif; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-GB;">synthesis of Ni/Al2O3 nanocomposites by milling at 200 rpm for 1.5 h. Extending the milling duration at lower rotational speeds yielded powders with nanoscale particle sizes. However, as observed under scanning electron microscopy and energy dispersive spectroscopy, a metallic matrix nanocomposite was formed via the mechanochemical reaction, and the crystallite size was estimated <span style="font-size: 12.0pt; line-height: 115%; font-family: ’Times New Roman’,serif; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-US;">using <span lang="EN-GB" style="font-size: 12.0pt; line-height: 115%; font-family: ’Times New Roman’,serif; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-GB;">the Williamson–Hall plot. Furthermore, <span style="font-size: 12.0pt; line-height: 115%; font-family: ’Times New Roman’,serif; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-US;">using differential scanning calorimetry plots, we <span lang="EN-GB" style="font-size: 12.0pt; line-height: 115%; font-family: ’Times New Roman’,serif; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-GB;">analy<span style="font-size: 12.0pt; line-height: 115%; font-family: ’Times New Roman’,serif; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-US;">s<span lang="EN-GB" style="font-size: 12.0pt; line-height: 115%; font-family: ’Times New Roman’,serif; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-GB;">ed the effect of milling on the temperatures of phase transformation and/or reduction reactions. <span lang="EN-GB" style="font-size: 12.0pt; line-height: 115%; font-family: ’Times New Roman’,serif; mso-ascii-theme-font: major-bidi; mso-hansi-theme-font: major-bidi; mso-bidi-theme-font: major-bidi; mso-ansi-language: EN-GB;">The tribological performance of the developed nickel metal matrix composite was examined by employing a ball-on-disc tribometer at various load conditions. Indeed, the friction coefficient increases with applied forces and decreases with milling. Comprehensive examinations of the worn surfaces were conducted through the utilization of a scanning electron microscope and a 3D optical profiler.